Loss of ARHGEF6 Causes Hair Cell Stereocilia Deficits and Hearing Loss in Mice - Zhu, Chengwen; Cheng, Cheng; Wang, Yanfei; Muhammad, Waqas; Liu, Shuang; Zhu, Weijie; Shao, Buwei; Zhang, Zhong; Yan, Xiaoqian; He, Qingqing; Xu, Zhengrong; Yu, Chenjie; et al. (Frontiers in Molecular Neuroscience, 2018)
ARHGEF6 belongs to the family of guanine nucleotide exchange factors (GEFs) for Rho GTPases, and it specifically activates Rho GTPases CDC42 and RAC1. Arhgef6 is the X-linked intellectual disability gene also known as XLID46, and clinical features of patients carrying Arhgef6 mutations include intellectual disability and, in some cases, sensorineural hearing loss. Rho GTPases act as molecular switches in many cellular processes. Their activities are regulated by binding or hydrolysis of GTP, which is facilitated by guanine nucleotide exchange factors and GTPase-activating proteins, respectively. RAC1 and CDC42 have been shown to play important roles in hair cell (HC) stereocilia development. However, the role of ARHGEF6 in inner ear development and hearing function has not yet been investigated. Here, we found that ARHGEF6 is expressed in mouse cochlear HCs, including the HC stereocilia. We established Arhgef6 knockdown mice using the clustered regularly interspaced short palindromic repeat-associated Cas9 nuclease (CRISPR-Cas9) genome editing technique. We showed that ARHGEF6 was indispensable for the maintenance of outer hair cell (OHC) stereocilia, and loss of ARHGEF6 in mice caused HC stereocilia deficits that eventually led to progressive HC loss and hearing loss. However, the loss of ARHGEF6 did not affect the synapse density and did not affect the mechanoelectrical transduction currents in OHCs at postnatal day 3. At the molecular level, the levels of active CDC42 and RAC1 were dramatically decreased in the Arhgef6 knockdown mice, suggesting that ARHGEF6 regulates stereocilia maintenance through RAC1/CDC42.